2020
DOI: 10.22541/au.158880203.33695479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rivers, not refugia, drove diversification in arboreal, sub-Saharan African snakes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For instance, we found distinct lineages of L . millsoni on either side of the Sanaga and Congo Rivers, and both rivers coincide with intra‐ and interspecific levels of divergence in a range of taxa including the ground dwelling long‐fingered frogs (Hirschfeld et al, 2015), swamp rats (Bohoussou et al, 2015), arboreal snakes (Allen et al, 2021), and chimpanzees (Hey, 2010). Likewise, our ENMs identify several regions within West and Central African rainforests as climatically suitable throughout the late Pleistocene to present day for L .…”
Section: Discussionmentioning
confidence: 92%
“…For instance, we found distinct lineages of L . millsoni on either side of the Sanaga and Congo Rivers, and both rivers coincide with intra‐ and interspecific levels of divergence in a range of taxa including the ground dwelling long‐fingered frogs (Hirschfeld et al, 2015), swamp rats (Bohoussou et al, 2015), arboreal snakes (Allen et al, 2021), and chimpanzees (Hey, 2010). Likewise, our ENMs identify several regions within West and Central African rainforests as climatically suitable throughout the late Pleistocene to present day for L .…”
Section: Discussionmentioning
confidence: 92%
“…Pirani et al (2019) indicated that divergence-time across river basins varies, suggesting that river barriers can be dynamic considering connection and isolation induced by climatic ameliorations. By contrast, forest-living snakes in the Congo River basin exhibit divergence across the river independent of isolation by climatic ameliorations (Allen et al, 2021). The strength of the dispersal barrier is, however, variable, being stronger where the river is wider (Allen et al, 2021).…”
Section: Rivers As a Biogeographic Barriermentioning
confidence: 99%
“…By contrast, forest-living snakes in the Congo River basin exhibit divergence across the river independent of isolation by climatic ameliorations (Allen et al, 2021). The strength of the dispersal barrier is, however, variable, being stronger where the river is wider (Allen et al, 2021). Similarly, in a recent study of 33 animal taxa along the Colorado River, Dolby et al (2019) suggested that rivers should be viewed as leaky barriers, that filter rather than prevent gene flow.…”
Section: Rivers As a Biogeographic Barriermentioning
confidence: 99%
“…There have since been other simulations purporting to show that NCPA has a high false positive rate, with the most recent being Panchal and Beaumont (2010). All of these are based on serious misrepresentations of NCPA, and when these misrepresentations are corrected, the type I error rate is at or below the pre-set level of 0.05 (Templeton, 2009, 2015, Allen et al, 2021. Finally, NCPA does not require a prior phylogeographic model, but rather phylogeographic inferences are built up directly from the data by retaining only statistically significant inferences.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Both Darwin and Wallace recognized the role of rivers in dividing populations and isolating them for periods of time sufficient to accumulate morphological differences between the populations they separate (Wallace, 1849;Darwin, 1872). Studies in many taxa, including frogs, birds, rodents, and primates, have elaborated on the river barrier hypothesis (Sick, 1967;Capparella, 1988;Ayres and Cluttonbrock, 1992;Patton et al, 1994;Lougheed et al, 1999;Aleixo, 2004;Nicolas et al, 2011Nicolas et al, , 2019Voelker et al, 2013;Kopuchian et al, 2020;Allen et al, 2021;de Fraga and Carvalho, 2021). In general, river size (width, flow-rate, discharge) is expected to positively correlate with indices of differentiation between populations separated by rivers.…”
Section: Introductionmentioning
confidence: 99%